Implementasi Microsoft Sway Pada Pembelajaran Jarak Jauh Di Kelas IV SDN 006 Loa Janan Ilir Tahun Pembelajaran 2020/2021 - Andi Alif Tunru; Rizka Dwi Putri G (SISTEMA: Jurnal Pendidikan, 2021)
This research was carried out with the aim of knowing how to implement Microsoft Sway in distance learning in class IV SDN 006 Loa Janan Ilir. This type of research is descriptive qualitative research. The subjects were students of class IV C SDN 006 Loa Janan Ilir, totaling 30 people. Data collection techniques using observation and documentation. The results showed that there was an increase in the activeness of students in distance learning using Microsoft Sway, and it was easier for students to understand the material given by the teacher. Thus it can be concluded that the implementation of Microsoft Sway can help teachers and students in carrying out learning during distance learning. Keywords: Implementation, Microsoft Sway, Distance Learning